Model development and initial characterization of Escherichia coli in the shellfish-producing area of Butrinti Lagoon - Renis Maçi; Fatmira Shehu; Enton Spaho; Bizena Bijo (Italian Journal of Food Safety, 2024)
The purpose of this research was to estimate the correlation between hydrochemicals and Escherichia coli contamination in Mytilus galloprovincialis by using multi-linear regression and statistically processing the monthly mean results. This study was conducted in the traditional cultivation of M. galloprovincialis, sampled and analyzed (n=136) for E. coli microbial analysis with ISO 16649-3. During the years 2015-2017, seawater was measured with a multiparameter apparatus, where four variables [dissolved oxygen (n=115), temperature (n=127), pH (n=115), salinity (n=127), and local area rainfall monitoring (n=23)] were taken into consideration. The results were compared and shown to have a significant correlation, allowing for the quantification of the impact resulting from adjustments made to the monthly mean computation. During the study period, statistical performance for each year was estimated R2=94.4% (2015), R2=46.8%, and R2=97.5% (2017).